2019
DOI: 10.1002/slct.201803850
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Sensitive Fluorescence Assay of DNA Polymerase Activity Using Cu2+ and Ascorbate as Signal Developers

Abstract: We report herein a label-free and turn-on fluorescence approach for detecting DNA polymerase activity. In the presence of DNA polymerase, the DNA primer could be elongated to produce one long double-stranded DNA (dsDNA). Then, the produced dsDNA acted as the template for in-situ synthesizing fluorescent copper nanoclusters (CuNCs) via Cu 2 +ascorbate reaction (10 min at room temperature), and the fluorescent intensity of the CuNCs was used to quantify the activity of DNA polymerase. In this strategy, cheap CuS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They showed that in the absence of MNase, dsDNA with the aid of sodium ascorbate served as a template for the formation of Cu NCs with excitation/emission peaks located at 340/570 nm. The fluorescence turn-on strategy based on DNA-templated synthesis of Cu NCs was also used for the activity detection of enzymes like T4 polynucleotide kinase phosphatase, 43 DNA polymerase 231 and uracil-DNA glycosylase (UDG). 46 Both dsDNA and ssDNA can act as a template for the synthesis of Cu NCs.…”
Section: H 2 O and H 2 O 2 Sensingmentioning
confidence: 99%
“…They showed that in the absence of MNase, dsDNA with the aid of sodium ascorbate served as a template for the formation of Cu NCs with excitation/emission peaks located at 340/570 nm. The fluorescence turn-on strategy based on DNA-templated synthesis of Cu NCs was also used for the activity detection of enzymes like T4 polynucleotide kinase phosphatase, 43 DNA polymerase 231 and uracil-DNA glycosylase (UDG). 46 Both dsDNA and ssDNA can act as a template for the synthesis of Cu NCs.…”
Section: H 2 O and H 2 O 2 Sensingmentioning
confidence: 99%